Аналіз привабливості євроінтеграції України через призму громадської думки - Бондаренко, О. І.; Bondarenko, O.I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
In the article the public opinion on Western vector of Ukraine’s integration was studied. The awareness of Ukrainian and European society about one another and their attitude was analyzed.
The Analysis of Ukraine's Attractiveness for Europe and the European Integration At-tractiveness for Ukraine through the lens of public opinion
О.І.Бондаренко, к.психол.н., доц. кафедри міжнародної інформації Хмельницького національного університету (Україна, м.Хмельницький)
Keywords: integration; surveys; public opinion; effects